2022
DOI: 10.1051/0004-6361/202244386
|View full text |Cite
|
Sign up to set email alerts
|

The crater-induced YORP effect

Abstract: Context. The Yarkovsky−O'Keefe−Radzievskii−Paddack (YORP) effect plays an important role in the rotational properties and evolution of asteroids. While the YORP effect induced by the macroscopic shape of the asteroid and by the presence of surface boulders has been well studied, no investigation has been performed yet regarding how craters with given properties influence this effect. Aims. We introduce and estimate the crater-induced YORP effect (CYORP), which arises from the concave structure of the crater, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…First, it has been shown that the magnitude and direction of the YORP torque are highly sensitive to small changes in the primary's shape, meaning that each landslide, mass shedding event, and natural impact could change the strength and direction of the YORP effect. This could make YORP spin-up effectively a random walk process and may significantly increase the amount of time required to build a secondary in orbit (Statler 2009;Cotto-Figueroa et al 2015;Zhou et al 2022). This effect may significantly decrease the efficiency of such a formation process, making a scenario in which the secondary forms from a single rotational disruption event more attractive.…”
Section: Previous Workmentioning
confidence: 99%
“…First, it has been shown that the magnitude and direction of the YORP torque are highly sensitive to small changes in the primary's shape, meaning that each landslide, mass shedding event, and natural impact could change the strength and direction of the YORP effect. This could make YORP spin-up effectively a random walk process and may significantly increase the amount of time required to build a secondary in orbit (Statler 2009;Cotto-Figueroa et al 2015;Zhou et al 2022). This effect may significantly decrease the efficiency of such a formation process, making a scenario in which the secondary forms from a single rotational disruption event more attractive.…”
Section: Previous Workmentioning
confidence: 99%
“…As a result, predicting even the instantaneous YORP value may be very difficult (this is the reason why the presently achieved YORP detections are often smaller than theoretically expected; see the latest compilation in the discussion section of Ďurech et al 2024). From a longterm perspective, the movement of boulders (Golubov & Krugly 2012) and formation of impact craters (Zhou et al 2022;Zhou & Michel 2024) could modify or even reverse the direction of the YORP torque. Building on the YORP's shape sensitivity, Bottke et al (2015) introduced the "stochastic YORP" concept and showed that it overall weakens the longterm effects of nominal YORP.…”
Section: Synchronization Of the Secondary Componentmentioning
confidence: 99%
“…However, accurately calculating the YORP effect on a real asteroid remains a challenge, as it has been demonstrated to be highly sensitive to surface topology (Statler 2009;Breiter et al 2009), such as uniform small-scale roughness (Rozitis & Green 2012), boulders (Golubov & Krugly 2012;Golubov et al 2014Golubov et al , 2021Ševeček et al 2015;Golubov 2017;Golubov & Scheeres 2019;Golubov & Lipatova 2022), and craters (Zhou et al 2022). Although the YORP torque caused by boulders and the tangential radiative force has been well studied, the YORP effect caused by concave structures has not yet been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…To account explicitly for the YORP torque caused by roughness and craters, Zhou et al (2022) developed a semi-analytical model that is computationally efficient for the crater-induced YORP (CYORP) torque. The CYORP torque is defined as the torque difference between the crater and the flat ground:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation